The Effect of Workplace Incivility On The Performance of Manufacturing Industry Employees: The Moderating Effects Of Collectivism Culture and Passive Leadership - Gustiawan, Deni; Purwanti, Winaya (Publikasi Indonesia, 2024)
The manufacturing industry in Indonesia is an important sector in the national economy. However, this industry is also faced with various challenges, one of which is incivility in the workplace. This discussion aims to observe the impact Workplace Incivility at the achievement of manufacturing industry employees in Indonesia with the moderating variables of collectivism culture and passive leadership. This research apply quantitative discussion techniques. Data was collected with surveys implementing questionnaires and literacy research. Data that was been obtained is then carried out using observations a regression test with SPSS program. The findings of the discussion show this Workplace Incivility has a negative influence on the performance of manufacturing industry employees in Indonesia. In addition, a culture of collectivism and passive leadership moderates the relationship among Workplace Incivility also employee performance.